(untitled) (KULT_online, 2023)
Marco Caracciolo’s Slow Narrative and Nonhuman Materialities focuses on the form and potential of slow narrative for an affective and embodied experience of climate change. With a variety of vivid close-readings, Caracciolo illuminates the narrative strategies that produce deceleration and convincingly shows how these are conducive to an experience of entanglements between the human and nonhuman world. His study proves to be an important contribution to (cognitive) narratology, phenomenological conceptions of narrative, and the environmental humanities as a whole.